Stilsko oblikovańe viziìe „Posledńih vremena``u srpskoì narodnoì poeziìi - Nikolić, Vidan (Stylistyka, 2021)
The work tends to classify the stylistic characteristics which can be found in those par- ts of Serbian folk poetry that deal with the motif of the “end of time” vision. The “end of time” is a Biblical topie about the curse and the finał judgement that will lead to the de- struction of the Earth due to the sins and lawlessness of the people living on it. The “end of time “vision consists of a longer or a shorter listing of the human lawlessness and the events that foretell the coming of the end. In this world destruction the four basie life sym- bols will disappear: the sheep and the wheat, the bee and the flower. In order to express the apocalyptic vision of the world disaster, a specific “scenario” is madę; the “scenario” in which the apocryphal picture of paradise and heli is given. That picture enabled the folk poet to produce specific poetic images with a lot of stylistic figu- res in a finely sharpened poetry.